Predictive value of platelet aggregation rate in hemodynamically significant patent ductus arteriosus in preterm infants - Ren, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2021)
Objective: To explore the predictive value of platelet aggregation rate in patent ductus arteriosus in preterm infants. Methods: This prospective nested case-control study enrolled 72 preterm infants with gestational age<32 weeks, who were admitted to Neonatal Intensive Care Unit of Xuzhou Central Hospital from August 2017 to October 2019. The echocardiography was performed on the 4th to 5th day after birth, and the preterm infants who met the diagnostic criteria of hemodynamically significant patent ductus arteriosus (hsPDA) were included into hsPDA group, and the control group was comprised of matched preterm infants with non-hsPDA according to the proportion of 1∶2. The basic characteristics of the preterm infants were recorded, and their complete blood counts and platelet aggregation function were examined. Clinical data were compared by student's t test and chi-square test between the two groups. The risk factors and their predictive values were analyzed by binary logistic regression analysis and receiver operating characteristic curve. Results: There were 24 preterm infants (16 boys) in the hsPDA group, and 48 (30 boys) in the control group. The incidence of neonatal respiratory distress syndrome (NRDS) grade II-IV in the hsPDA group was higher than that in the control group (67% (16/24) vs. 27% (13/48), χ²=10.422, P=0.001). The thrombocytocrit and adenosine diphosphate-induced platelet aggregation rate in the hsPDA group were lower than those in the control group (0.002 1±0.000 9 vs. 0.002 8±0.000 9, 0.21±0.10 vs. 0.32±0.07, t=-3.043 and -5.093, P=0.004 and <0.01, respectively); while the platelet volume in the hsPDA group was greater than that in the control group ((10.3±2.4) vs. (9.2±2.0) fl, t = 2.713, P = 0.033). The other platelet parameters (platelet count, platelet distribution width, and large platelet ratio) and platelet aggregation rate induced by other inducers (collagen, epinephrine and arachidonic acid) were not significantly different between the two groups (all P>0.05). The low platelet aggregation rate induced by adenosine diphosphate and low thrombocytocrit were independent risk factors for hsPDA in preterm infants (OR=4.525 and 3.994, 95%CI: 1.305-15.689 and 1.143-13.958, respectively). And the adenosine diphosphate-induced platelet aggregation rate had moderate predictive value for hsPDA in preterm infants, as the area under the receiver operating characteristic curve was 0.809, and the cutoff value was 0.245 with 0.67 sensitivity and 0.86 specificity. Conclusions: Poor platelet aggregation function and low thrombocytocrit are independent risk factors for hsPDA in preterm infants with gestational age<32 weeks. Low platelet aggregation rate induced by adenosine diphosphate has moderate predictive value for hsPDA patency